Structural relationship model of causes and effects of construction changes in UAE construction industry - Al Ameri, Abdulla Eissa Saleh (2021)
Studies have shown that changes happened in late construction project phases contributed in major failure of a project. Hence, this study is intended to develop structural relationship model of causes and effects for construction changes from the perspective of the UAE construction practitioners. This study was carried out using a quantitative approach with the respondents coming from managerial level working that are working on mega construction projects. The questionnaire was validated using pilot study by 28 construction experts with the outcome that shown that all the 58 causes were categorised into 3 groups (client, contractor, and consultant) and 48 effects were categorised into 3 groups (time overrun, cost overrun, and quality assurance). Next, the actual survey came with 100 valid responses and the data collected from the survey were analysed descriptively. The results found that the most influential construction change causes affecting a project’s performance is the lack of coordination, while the most challenging construction changes effects were the delay in completion. The collected data were further tested by using PLS-SEM relationship model and found that the model has achieved all the assessment criteria with goodness-of-fit index of 0.404 which validated the model. It also found that the relationship of construction changes triggered by contractor has significant effect on time, cost and quality of the project. To ensure that the model is applicable to the UAE construction industry, face validation by selected construction experts was conducted and found that all experts agreed on the model. Hence, this study has shown the importance of identifying construction change causes and effects that it could be useful being practiced by the UAE construction industry.